Handbook of transport systems and traffic control edited by Kenneth J. Button, David A. Hensher. - Hensher, David A., 1947-; Button, Kenneth, 1948- (Handbooks in transport, 2001)
This book discusses transport systems and the implementation of related public policy - a relevant topic with contemporary traffic congestion, environmental intrusion, transport safety, and budget issues. It is a resource for both experienced researchers and those new to the field.